If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -10a = 8 + -9a Solving 7 + -10a = 8 + -9a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '9a' to each side of the equation. 7 + -10a + 9a = 8 + -9a + 9a Combine like terms: -10a + 9a = -1a 7 + -1a = 8 + -9a + 9a Combine like terms: -9a + 9a = 0 7 + -1a = 8 + 0 7 + -1a = 8 Add '-7' to each side of the equation. 7 + -7 + -1a = 8 + -7 Combine like terms: 7 + -7 = 0 0 + -1a = 8 + -7 -1a = 8 + -7 Combine like terms: 8 + -7 = 1 -1a = 1 Divide each side by '-1'. a = -1 Simplifying a = -1
| 6m^3n^-6/30n^-5m^-1 | | 3.4=22.6-6x | | (5z-7)(5+z)=0 | | a^2+6a+0=0 | | 15x-29=106 | | 5t=-(5-7)2+90 | | 12a^-4/4a^-6 | | -2-13.8x=-8x-(6x+1)xis | | (a^2x)+(a-1)=(a+1)x | | x^2-12x+20=-6 | | x=(w-5)(w+5) | | 34=2x^2+26x+-4 | | y=2x^2+26x-4 | | y=-800x-80ln(x) | | 4m+2m(m-3)=6 | | y=-2/9x-3 | | (8+z)(2z+9)=0 | | 4(2+a)=72 | | 20x^16-6x^13/-2x^10 | | -8y+4=-4(y-6) | | 6x(10-6x)=35-5(6x+1) | | c-3=28 | | -42=-7/6u | | 16p^2+64=0 | | 7x+9=11x+21 | | (7x^2-15)(7x^2-15)= | | xsquared+7x+1=0 | | 2x^2+6x+2.5=0 | | 40-1/22(4c)=30-1/22(3c) | | 0.4=x/30 | | 2x^2+6x+2.25=0 | | 7log(x)=3 |